El viaje y la historia: el mito de al-Ándalus en los modernos viajeros árabes a España - Paradela, Nieves (Revista de Filología Románica, 2006)
This work illustrates the reasons that urged some Arab travellers in the XIXth and XXth centuries to visit the most representative places of al-Ándalus, underlining its stages as a Golden Age, as a moment of decline or of rebirth, from a perspective far away from the usual topics, and looking at the past since modernity.